THE STUDENT’S PERCEPTION OF CONSTRUCTIVE FEEDBACK GIVEN BY INSTRUCTORS IN THE PROSTHODONTIC’S CLINICAL SKILLS LEARNING - Citra Insany Irgananda; Adistia Noor Khairani (Erudio Journal of Educational Innovation, 2019)
Skills lab is a program in the Standar Kompetensi Dokter Gigi Indonesia (SKGI) that has to be carried out by dentistry students. One of them is the Prosthodontics skills lab. A constructive feedback is expected to be provided by the instructor to the students in the skills lab. This research was aimed to evaluate students’ perception about the constructive feedback given by the instructor during the Prosthodontics skills lab in the Dentistry Faculty of Universitas Brawijaya. This study used mixed methods combining the quantitative and qualitative methods. The quantitative data showed that a majority of Universitas Brawijaya’s class of 2015 dentistry students (55.9%) assumed that the feedback given by the instructor was moderate. The rest stated that they received a level 3 feedback which is feedback in form of giving correct answers and their detailed explanation. The qualitative data showed that the constructive feedback was motivation, improvement, and recommendation that the students received. The correct way of giving feedback according to the respondents’ perception is by giving explanation, positive expressions, constructive, honest, motivational, and giving demos. The benefits are as an evaluator, motivator, and a way to show students’ mistakes. The respondents’ experience during the Prosthodontics skills lab is receiving good feedback, understanding the presence of different perceptions among instructors, and understanding that there are also instructors that do not give guidance. According to Universitas Brawijaya’s class of 2015 dentistry students, the similarity in perception among instructors in giving feedback, the delivery of the feedback, the need of videos and demo during skills lab, and punctuality in the Prosthodontics skills lab need to be addressed.